Knowledge, attitudes, and practices towards artificial intelligence among young pediatricians: A nationwide survey in France - Perrier, Emma; Rifai, Mahmoud; Terzic, Arnaud; Dubois, Constance; Cohen, Jérémie F. (Frontiers in Pediatrics, 2022)
Objective To assess the knowledge, attitudes, and practices (KAP) towards artificial intelligence (AI) among young pediatricians in France. Methods We invited young French pediatricians to participate in an online survey. Invitees were identified through various email listings and social media. We conducted a descriptive analysis and explored whether survey responses varied according to respondents’ previous training in AI and level of clinical experience (i.e., residents vs. experienced doctors). Results In total, 165 French pediatricians participated in the study (median age 27 years, women 78%, residents 64%). While 90% of participants declared they understood the term “artificial intelligence”, only 40% understood the term “deep learning”. Most participants expected AI would lead to improvements in healthcare (e.g., better access to healthcare, 80%; diagnostic assistance, 71%), and 86% declared they would favor implementing AI tools in pediatrics. Fifty-nine percent of respondents declared seeing AI as a threat to medical data security and 35% as a threat to the ethical and human dimensions of medicine. Thirty-nine percent of respondents feared losing clinical skills because of AI, and 6% feared losing their job because of AI. Only 5% of respondents had received specific training in AI, while 87% considered implementing such programs would be necessary. Respondents who received training in AI had significantly better knowledge and a higher probability of having encountered AI tools in their medical practice (p < 0.05 for both). There was no statistically significant difference between residents’ and experienced doctors’ responses. Conclusion In this survey, most young French pediatricians had favorable views toward AI, but a large proportion expressed concerns regarding the ethical, societal, and professional issues linked with the implementation of AI.